Pengaruh Pendidikan Kesehatan Teknik Sadari terhadap Pengetahuan dan Sikap Deteksi Dini Kanker Payudara pada Remaja: The Impact of Health Education on Breast Self-Examination (BSE) Technique on Knowledge and Attitudes Regarding Early Breast Cancer Detection Among Adolescents - Florentina, Florentina; Yuliza, Emi; Eni Lestari, Nur (Journal of Nursing Education and Practice, 2024)
Introduction: Breast cancer is a malignant tumor that affects the glandular tissue, ductal glands, and supporting structures of the breast. Breast Self-Examination (BSE) is an early detection method aimed at increasing women's awareness of their own breast condition, enabling them to recognize early signs and symptoms such as changes in size, texture, and shape. Early detection is crucial for effective treatment, especially when the cancer is found in its initial stages. Objective: This study aims to determine the effect of health education on adolescents’ knowledge and attitudes regarding BSE. Method: This study employed a one-group pretest-posttest design with a sample of 17 adolescents. The research instruments included a standard operating procedure (SOP) and a questionnaire containing questions related to knowledge and attitudes before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. Results: Prior to the health education intervention, the average level of knowledge and attitudes among adolescents regarding BSE was categorized as fairly good, with percentages of 52.9% and 58.8%, respectively. After the intervention, there was a significant increase in knowledge and attitudes, with posttest percentages of 82.4% and 52.2%, respectively. The Wilcoxon test yielded an Asymp. Sig. (2-tailed) value of 0.000, indicating that the hypothesis was accepted, as the significance value was less than 0.05. Conclusion: Health education significantly influenced the improvement of adolescents’ knowledge and attitudes regarding BSE. This improvement indicates that health education is effective in raising awareness among adolescents about the importance of early detection of breast cancer through BSE.